2021
DOI: 10.18488/journal.24.2021.101.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Survival Quantile Regression Analysis of Covid-19 in Rivers State, Nigeria

Abstract: Survival quantile regression Cox proportional Hazard model Accelerated failure time model Log-rank test Survival function and censoring. Coronavirus 2019 (Covid-19) cases in Rivers State, Nigeria are on the increase day by day. It became imperative to investigate the survival rate of covid-19 patients in this state. The survival quantile regression was applied assuming right censoring to estimate the effect of age, sex, fever, anosmia, comorbidity, and cough on the survival time of patients. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, these associations were weak. [7] In her study on survival of COVID-19 patients in rivers state, Nigeria concluded that fever, comorbidity, and anosmia are the major factors that affect the survival time of COVID-19 patients in Rivers State, Nigeria. The age groups most affected by COVID-19 in Nigeria, as of June 30th 2020, were 21-50 years with a peak infection among 31-40 years [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, these associations were weak. [7] In her study on survival of COVID-19 patients in rivers state, Nigeria concluded that fever, comorbidity, and anosmia are the major factors that affect the survival time of COVID-19 patients in Rivers State, Nigeria. The age groups most affected by COVID-19 in Nigeria, as of June 30th 2020, were 21-50 years with a peak infection among 31-40 years [6].…”
Section: Introductionmentioning
confidence: 99%